2001
DOI: 10.1054/bjoc.2000.1689
|View full text |Cite
|
Sign up to set email alerts
|

Addition of high-risk HPV testing improves the current guidelines on follow-up after treatment for cervical intraepithelial neoplasia

Abstract: We assessed a possible role for high-risk human papillomavirus (HPV) testing in the policy after treatment for cervical intraepithelial neoplasia (CIN) 2 or 3 (moderate to severe dysplasia). According to the Dutch guidelines follow-up after treatment consists of cervical cytology at 6, 12 and 24 months. Colposcopy is only performed in case of abnormal cervical cytology. In this observational study 184 women treated for CIN 2 or 3 were prospectively monitored by cervical cytology and high-risk HPV testing 3, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
2
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 15 publications
8
124
2
5
Order By: Relevance
“…One study recommended including HR HPV test to monitor women initially treated for CIN 2 or 3. 20 They suggested that all women should be tested at 6 and 24 months after treatment, and should only be referred for routine cervical cancer screening when these tests are negative on both visits. They evaluated the predictive value of the follow-up HPV test in patients treated for CIN 2 or 3.…”
Section: Discussionmentioning
confidence: 99%
“…One study recommended including HR HPV test to monitor women initially treated for CIN 2 or 3. 20 They suggested that all women should be tested at 6 and 24 months after treatment, and should only be referred for routine cervical cancer screening when these tests are negative on both visits. They evaluated the predictive value of the follow-up HPV test in patients treated for CIN 2 or 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, the average length of a hrHPV infection is 6-14 months. [11][12][13][14] Moreover, meta-analyses of women with ASCUS and LSIL cytology have reported rates CIN, cervical intraepithelial neoplasia; hrHPV, high-risk human papillomavirus; LLETZ, large loop excision of the transformation zone. *Over 3 years following detection by management policy or at exit examination (for further details, see reference 39 ).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…[8][9][10] However, HPV infections are common, and most are transient, with a median duration of 6-14 months. [11][12][13][14] Hence there is a need for rigorous evaluation of this potential application of HPV testing.…”
Section: Introductionmentioning
confidence: 99%
“…Most other studies are prospective with fairly short follow up periods, a small number of patients and a minimal number of recurrences. 13 , 27 , 28 A Dutch study 29 reported high negative predictive value of post-treatment HPV-test, but only two women in this material developed high grade CIN later than 2 years after initial treatment. However, with a case-control design, Cruickshank and colleagues 30 had results in close concordance with ours.…”
Section: Discussionmentioning
confidence: 88%